Epigenetic modulation of immune synaptic-cytoskeletal networks potentiates γδ T cell-mediated cytotoxicity in lung cancer - Rueyhung R. Weng (Nature Portfolio, 2021)
Gamma delta (γδ) T cells have potential for use in immunotherapy against tumours. Here, the authors demonstrate that treatment of tumours with DNA methyltransferase inhibitors modulates cytoskeleton arrangements, upregulates adhesion molecules and increases tumour killing by γδ T cells.